Heterogeneity of aortic disease severity in patients with Loeys–Dietz syndrome. Issue 8 (4th February 2016) - Teixidó-Tura, Gisela; Franken, Romy; Galuppo, Valentina; Gutiérrez García-Moreno, Laura; Borregan, Mar; Mulder, Barbara J M; García-Dorado, David; Evangelista, Artur
Abstract : Objective: This study aimed to determine aortic disease severity in patients with Loeys–Dietz syndrome (LDS). Methods: Thirty-three patients with LDS diagnosed and followed up at our unit were included. After reviewing all family trees, 25 deceased family members with clear clinical suspicion of having had LDS were also included. Clinical presentation, aortic dilation rate by echocardiography and age at aortic surgery, dissection or death were determined. Results: Median aortic diameter at diagnosis was 36 mm, 43% of the patients aged >40 years had a z-score <2. Median aortic root dilation rate was 0.67 mm/year (maximum 2.0 mm/year) over a median follow-up of 2 years (IQR 1.0–4.0). In the global cohort, 31/58 patients reached a clinical endpoint; 19% death, median age: 52 years; 14% dissection, median age: 36 years; 21% aortic surgery, median age: 53 years. As expected, probands had a higher z-score (2.9 vs 1.5, p=0.019) and more often required aortic surgery (33.4% vs 18.2%, p=0.035) compared with family members. TGFBR2 carriers had a higher z-score compared with TGFBR1 carriers (3.2 vs 1.5, p=0.034) and younger age at aortic surgery (HR 4.9, 95% CI 1.5 to 123, p=0.026). Craniofacial severity index was inversely correlated with age at first event (r=−0.765, p=0.045). Conclusions: Although paediatric patients were not properly represented in our cohort, our patients with LDS presented a significant heterogeneity in the severity of aortic disease with large intrafamilial and interfamilial variability, aortic root aneurysm were less frequent and aortic complications less premature than previously depicted. Furthermore, aortic dilation rate was similar to that reported in Marfan syndrome and aortic root diameters appear to be larger in TGFBR2 carriers.